Rethinking Broken Homes: Teachers' Perceptions and Their Implications for Islamic Education Counseling - Sapari; Yusuf MZ; Khorotul Anizah; Salsabila Nabila; Laila Nur Sa’adah (Lentera Pendidikan: Jurnal Ilmu Pendidikan dan Keguruan Islam, 2026)
This qualitative study examines educators' perceptions of the meaning of Broken Home and its impacts at SMA Negeri 1 Astanajapura Cirebon. Employing interviews and documentation studies with five teachers, the research reveals that Broken Home is perceived not merely as parental divorce, but encompasses broader family dysfunctions including disharmony, parental loss, and lack of affection. The observed educational impacts involve juvenile delinquency, learning disengagement, declining academic performance, social withdrawal, and intense jealousy. Consequently, the study underscores the necessity for a holistic Islamic guidance and counseling approach, prioritizing emotional support and spiritually-grounded interventions.